TIMURID PRINCES IN THE SOURCE “MUJMALI FASIHI” (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the genealogical and personographic information regarding the Timurid princes (mirzas) found in the work "Mujmali Fasihi" by Fasih Ahmad ibn Jalaliddin Muhammad al-Khawafi. The author covers the issues of systematizing the data from the source and creating a database based on them. The study defines the chronological framework of the Timurid genealogy and examines various types of historical information (birth, political and military activities, construction works, etc.) related to Amir Timur and his descendants, categorized for further analysis.